Kinetic Study on Removal of Sulphur Mustard on Granular Activated Carbon from Aqueous Solution - Baghel, Anuradha; Singh, Beer (Defence Life Science Journal, 2016)
Sulphur mustard is a powerful blister agent and has been worked as a chemical warfare agent. No specific antidote is available for its wound. Therefore, adsorptive removal is an effective way of removal. Here, adsorptive removal of sulphur mustard from aqueous solution was studied on activated carbon and screened out MeOH : H2O (1 : 1) solution as a good solvent than others used solvent. Adsorption isotherm of sulphur mustard was compared with its hydrolysis in the same solution. Kinetics of sulphur mustard removal on carbon from aqueous solution was found to be slower than hydrolysis and follow pseudo first order kinetics with the rate constant 5.04 X 10–3 min-1 and half life 137.5 min. The hydrolysis of sulphur mustard in MeOH : H2O (1 : 1) solution was found to be following the pseudo first order kinetics with the rate constant 8.68 x10-3 min-1 and half life 79.8 min.